1947
DOI: 10.1038/icb.1947.14
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Plasma Coagulation Time and Prothrombin Concentration

Abstract: The estimation of the clotting time of plasma using thromboplastic agents and calcium ions is a valuable test for the assessment of haemorrhagic tendencies, but it is not an indication of frothrombin concentration in a chemical sense. Terms such as "prothrombin time," "accelerated clotting time" and "prothrombin activity'' suggested by various authors all emphasize this point. On the other hand, the so-called two-stage technique elaborated by Warner, Brinkhous ana Smith (1936) allows a quantitative estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1948
1948
1958
1958

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The conclusion was strengthened by experiments in which heparinized plasma was treated with BaSo4 to remove prothrombin as described by Fantl & Nance (1947). 'Plasma so treated released histamine in the presence of antibody and antigen as effectively as did untreated plasma.…”
Section: Rabbit Blood Systems (1) Histaminase In Plasmamentioning
confidence: 99%
“…The conclusion was strengthened by experiments in which heparinized plasma was treated with BaSo4 to remove prothrombin as described by Fantl & Nance (1947). 'Plasma so treated released histamine in the presence of antibody and antigen as effectively as did untreated plasma.…”
Section: Rabbit Blood Systems (1) Histaminase In Plasmamentioning
confidence: 99%
“…Quick (1943) assumes that an essential component of the prothrombin molecule, called prothrombin A, disappears during storage.P rom the study of isolated prothrombin both from fresh and stored plasma it could be shown, however, that prothrombin is the only precursor of thrombin (Seegers, Loomis andVandenbelt, 1945 andNance, 1946). However, normal plasma eontains in the globulin fraction, a factor capable of accelerating thrombin formation, Fantl and Nance (1948), and this principle has been isolated by OAvren (1947) and termed Factor V. Ware, Guest and Seegers (1947) confirmed the presence of prothrombin accelerator in beef plasma. The speed of thrombin formation is dependent, in addition to prothrombin, upon the concentration of prothrombin accelerator.…”
Section: Discussionmentioning
confidence: 99%
“…The details for these procedures are given by Tantl and Nance (1948). Fibrinogen and other protein estimations were carried out by a biuret technique as indicated previously (Fantl and Nance, 1947). In Table 1 the results obtained from specimens which had been stored from two to seven weeks are recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually serum from two donors was pooled. BaCO3 was freshly prepared according to Fantl & Nance (1947); BaSO4 was prepared from equivalent amounts of Ba(OH)2 and dil. H,S04, and washed with distilled water until neutral.…”
Section: Experimental Materials8mentioning
confidence: 99%